OVERLAY SEBAGAI MODEL PEMBELAJARAN DALAM MATA KULIAH SIG (SISTEM INFORMASI GEOGRAFIS) GUNA MENEMUKAN INFORMASI GEOSPASIAL BARU - Tjahyono, Heri (Lembaran Ilmu Kependidikan, 2007)
The aims of this investigation were a) to make a simple lerning model aboutoverlay with Arc View program in order to find a new geospatial information, b) toincrease lerning activity on Geography Information System (SIG) subject, throughCTL-based approach. The subject of this research is 35 students of 6th semester atGeography Education Program of Social Faculty of Semarang State University(UNNES). The location of this observation is in the Geography Information SystemLaboratory of Social studies of UNNES has bee done too field research outside thelaboratory. This is an action research, consibting of 2 cyolus. The result shows that, inthe first cycle a) There were 8 students still confused in using Arc View 3.3 Program,b) 12 students were make 3 basic maps, c) and only is students who succeeded infinishing overlay task. the second cycle show that, a) 2 students can make digitallymap, b) 6 students can make 3 basic map, c) and 27 students succeed in finishing SIGpractical overlay task in finding a new geospatial information.Kata kunci: Overlay, SIG, informasi geospatial baru